Improvement Of School Image And Student Parents' Interest To Choose A School Influenced By Product Strategies, Promotions And Prices In Sd Muhammadiyah 5 Porong - Kusnaini Sulchan; Hadiah Fitriyah Rizal (Indonesian Journal of Law and Economics Review, 2021)
The research objectives of this thesis are to find out and analyze products, promotions and prices that affect the school's image, parents' interest in choosing schools and to find out and analyze school image as a mediator variable capable of influencing the relationship between product, promotion, price and parents' interest in choosing schools at SD Muhammadiyah 5 Porong. This research belongs to the type of quantitative research and uses descriptive statistical analysis. Researching on a particular population or sample. Data collection using a limited questionnaire method. Respondents were the guardians of the students of SD Muhammadiyah 5 Porong as many as 125 people. Validity test analysis. To test the validity and reliability of the data, the researcher used the W-Start program. Hypothesis test analysis. Analysis of the relationship between variables will be carried out by path analysis assisted by the SPSS version 21 windows program. The results of the SPSS program analysis show that the influence of Product, Promotion, and Price Factors together in creating School Image is 65%. Meanwhile, the other 35% are influenced by other factors.